(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This study dealt with a unique Islamic personality who had a profound impact on the renaissance of Islamic society. He was mentioned in biographies, histories, and modern books that deal with the personality of the follower Uwais al-Qarni. We discussed his name, surname, and lineage, as we discussed his conversion to Islam, and how he was able to influence Islam in the depths of his soul and his love and longing to see his noble Prophet Muhammad. Except God) No, he could not do that to take care of a nation and take care of it. He received great attention from the Prophet in the narrations mentioned in this research. He also showed us his forms of asceticism, austerity, and staying away from the pleasures of the world and its desires until he achieved the honor of martyrdom among the people. The hands of Imam Ali bin Abi Talib on the Day of Siffin Al-Tabi’i Uwais Al-Qarni, his name, lineage, conversion to Islam, the Prophet’s hadiths about him, and his martyrdom in Siffin